A construção do currículo na perspectiva popular crítica das falas significativas às práticas contextualizadas - Silva, Antonio Fernando Gouvêa da (2004)
Starting from teaching experience in municipal and state public schools, out of my work as a pedagogical assistant at São Paulo Municipal Secretariat of Education (from 1989 to 1992) and, later, in different city administrations all over Brazil, I intend to characterize organizational moments for curricular reorientation movements. The analyzed political-pedagogical proposition is the Interdisciplinary Project through Generative Theme, understood as a process of permanent and collective formation of educators, involving all the school community, aiming at seeking the overcoming of the dichotomy between theory and practice from the conflicts and contradictions deeply experienced in the public school context. The contextualized participation of the citizens in the construction of their pedagogical practices is a political, social-cultural and epistemological demand for the qualification of the “educative making” in the different moments of the curricular construction process: from the characterization of difficulties faced in the quotidian of the conventional school to the pedagogical activities preparation moment for the classroom, being these organized from the selection of significant speeches of the community, generative themes systemized in networks - which they try in a dialetic way, to articulate different dimensions of the social-cultural reality - and from pertinent fragments of the universal systemized knowledge, selected by educators of different areas. As a result, the perspective that must guide this process of curricular construction is based on ethical, pedagogical, political and epistemological references, on the Critical Theory and on the praxis of the Popular and Liberating Education, in which the emancipator commitment guides the “dialogic making” in the construction of a critical popular curriculum. Lastly, I elaborate on the relations between these movements and the curricular educational politicies that have unchained them, in order to characterize the advances and difficulties observed in the analyzed practices and the necessary conditions for their implementation to happen in a coherent form, effectively contributing for the construction of an independent school community, committed with the transformation of the social-cultural reality in which it is inserted